Phosducin Regulates Secretory Activity in TT Line of Thyroid Parafollicular C Cells - Piotrowska, U.; Adler, G.; Kozicki, I. (Hormone and Metabolic Research, 2015)
The endocrine activity of the thyroid gland is accomplished by its follicular and parafollicular cells. In these cells, numerous G proteins-dependent pathways are active and potentially could be regulated by a 33-kDa cytoplasmic protein phosducin, which interacts with the Gβ subunit and may compete with Gα or Gβγ dimer effectors. Significant expression of phosducin has been shown in the retina, pineal gland, and some neurons. Here, we studied postoperative thyroid tissue samples collected from patients with nodular goiter and 2 thyroid-derived cell lines for the presence of phosducin. Using reverse transcription PCR with product sequencing and highly sensitive immunodetection we identified phosducin mRNA and protein in the thyroid gland and parafollicular C TT cells, but not in the follicular Nthy-ori 3-1 cell line. We also observed that siRNA-mediated silencing of phosducin gene expression decreased Ca2+-stimulated secretion of calcitonin and serotonin by TT cells.
Keywords: calcium; calcitonin; serotonin; medullary thyroid carcinoma TT cells; phosducin; thyroid